Antitumour effect of fever range whole-body hyperthermia with curcumin in breast cancer - Saim, Hanim (2020)
Breast cancer is a complex and heterogeneous disease, and one of the major types of cancer among females worldwide. In 2011, breast cancer accounted for 32.1% (18,206) of all cancer among females in Malaysia and the prevalence has been increasing since then. Current treatments of breast cancer include surgery, radiotherapy, endocrine therapy, biologic therapy, hormone therapy, chemotherapy, thermotherapy (hyperthermia), or a combination of these regimens. Hyperthermia is the procedure of elevating the temperature of a part of or the whole body to be above normal for a definite period of time using external and internal heating devices. Curcumin is a hydrophobic polyphenol, a dietary phytochemical, and a principle active ingredient derived from turmeric. Curcumin has been traditionally used for centuries as a food additive and as active agent in traditional medication. Hyperthermia given locally or whole body is often delivered as management of breast cancer besides chemotherapy. Even though chemotherapy provides survival advantages for many women with breast cancer, there are probable adverse effects and toxicity to the patients treated with chemotherapy. Due to the severe side effects of chemotherapy and the elevated death rate related to cancer, many cancer patients seek for complementary and alternative medicines (CAM), comprised of natural herbal medicines and plants as a method of treatment. Thus, this research was conducted to combine hyperthermia with curcumin as an alternative treatment of breast cancer. The effects of a combination treatment consisting of whole-body fever-range hyperthermia with curcumin on tumour growth were examined in this study. BALB/C mice were inoculated with EMT6 breast cancer cells subcutaneously and assigned to four treatment groups: (i) untreated (control), (ii) orally curcumin (50mg/kg body weight) (CUR), (iii) twice fever-range whole-body hyperthermia 39.0°C (± 0.5) for 15 minutes (FRWBH), (iv) orally curcumin (50mg/kg body weight) and twice fever-range whole-body hyperthermia 39.0°C (± 0.5) for 15 minutes (FRWBH+CUR). Following the treatment, mice body weight and tumour volume were measured throughout 28 days of experiment. The hematological parameters such as hemoglobin (Hb), platelet (PLT), red blood cells (RBC), white blood cells (WBC), lymphocytes (LYM) and neutrophils (NEUT), platelet - lymphocyte ratio (PLR) and neutrophil-lymphocyte ratio (NLR) were investigated at the end of experiment (day-28). Median survival time was determined for each group. The results presented that the tumour growth inhibition in combination treatment (FRWBH+CUR) was 82.91% with a significant difference (p=0.0440) compared to control. Mice treated with FRWBH+CUR had the longest median survival time which was 42 days. FRWBH+CUR treatment was well tolerated and safe to the mice with significance difference in percentage body weight gain was observed compared to control (p=0.001) up to 28 days of experiment. Even though there was frequent occurrence of the normal complications of cancer such as anaemia and thrombocytopenia in the group that received FRWBH+CUR treatment, PLR and NLR results indicated that the combination treatment (FRWBH+CUR) give better prognosis outcome than single treatment. As a conclusion, treatment of fever-range whole-body hyperthermia with curcumin (FRWBH+CUR) exhibited good antitumour effect in breast cancer-induced mice and this treatment has the potential as an alternative treatment of breast cancer.